The Influence of Guidance To Solve Problem In English Learning at SMP Al Akbar Brondong Lamongan - Rohmat Qosyim (Jurnal Pendidikan Islam, 2018)
Abstract: Teachers sometimes are amazed at the extent to which a child’s undesirable habit patterns can be recondit ioned through the efforts of understanding teachers. At the same time, home influences may be so strong that there is little that teachers and counselors can do for the child unless he can be removed from unhealthful home surroundings. In most states, the parents have the legal right to device where their child shall live. Hence school people are helpless in such situations unless, by court action, the child is placed in an institution or foster home because of extreme parental neglect of or cruelty to the child, or gross immoral behavior on the part of one or both parents. Based on the background, the writer wants to do classroom action research with the title “The Influence of Guidance to Solve Problem in English Learning at SMP Al Akbar Brondong”